Comparison of whole egg v. egg white ingestion during 12 weeks of resistance training on skeletal muscle regulatory markers in resistance-trained men. Issue 10 (28th November 2020) - Bagheri, Reza; Hooshmand Moghadam, Babak; Jo, Edward; Tinsley, Grant M.; Stratton, Matthew T.; Ashtary-Larky, Damoon; Eskandari, Mozhgan; Wong, Alexei
Abstract: Eggs are considered a high-quality protein source for their complete amino acid profile and digestibility. Therefore, this study aimed to compare the effects of whole egg (WE) v . egg white (EW) ingestion during 12 weeks of resistance training (RT) on the skeletal muscle regulatory markers and body composition in resistance-trained men. Thirty resistance-trained men (mean age 24·6 (sd 2·7) years) were randomly assigned into the WE + RT (WER, n 15) or EW + RT (EWR, n 15) group. The WER group ingested three WE, while the EWR group ingested an isonitrogenous quantity of six EW per d immediately after the RT session. Serum concentrations of regulatory markers and body composition were measured at baseline and after 12 weeks. Significant main effects of time were observed for body weight (WER 1·7, EWR 1·8 kg), skeletal muscle mass (WER 2·9, EWR 2·7 kg), fibroblast growth factor-2 (WER 116·1, EWR 83·2 pg/ml) and follistatin (WER 0·05, EWR 0·04 ng/ml), which significantly increased ( P < 0·05), and for fat mass (WER –1·9, EWR –1·1 kg), transforming growth factor- β 1 (WER –0·5, EWR −0·1 ng/ml), activin A (WER –6·2, EWR –4·5 pg/ml) and myostatin (WER –0·1, EWR –0·06 ng/ml), which significantly decreased ( P < 0·05) in both WER and EWR groups. The consumption of eggs absent of yolk during chronic RT resulted in similar body composition and functional outcomes as WE of equal protein value. EW or WE may be used interchangeably for the dietary support of RT-induced muscular hypertrophy when protein intake is maintained.